Modele edukacji osób starszych - Adamczyk, Monika Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Opracowanie prezentuje teoretyczne podstawy edukacji pozaformalnej i nieformalnej osób starszych. Szczególną uwagę poświęcono modelom edukacji seniorów realizowanym na uniwersytetach trzeciego wieku (UTW). W artykule zaprezentowano 5 modeli funkcjonowania UTW na świecie oraz przybliżono zasady i formy kształcenia ustawicznego w Polsce.

The paper presents the theoretical foundations of non-formal and informal education. Particular attention was given to the different models of senior education pursued at universities of third age in the world. The article discusses five models concerning the functioning of universities of third age all over the world. It also show an outline of the forms and principles of continuing education in Poland.
Models of Education for Elderly People
Keywords: starość; osoby w starszym wieku; kształcenie ustawiczne; model UTW; uniwersytety trzeciego wieku; age; elderly; life long learning; model of the third age university; universities of the third age